2017
DOI: 10.1016/j.jpag.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study

Abstract: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
4
21
2
Order By: Relevance
“…33e35 In our With adnexal pathology, recurrence rates of up to 12% have been reported; it appears to be even higher among premenarchal girls found to have otherwise normal ovaries and fallopian tubes. 13,19,38,40,41 In our cohort, there was a recurrence rate of 3.4% and although no association could be made regarding pubertal status, it was noted that none had pathologic lesions with the initial torsion.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…33e35 In our With adnexal pathology, recurrence rates of up to 12% have been reported; it appears to be even higher among premenarchal girls found to have otherwise normal ovaries and fallopian tubes. 13,19,38,40,41 In our cohort, there was a recurrence rate of 3.4% and although no association could be made regarding pubertal status, it was noted that none had pathologic lesions with the initial torsion.…”
contrasting
confidence: 59%
“…Nonetheless, experienced surgeons suggest that oophoropexy can be offered in the setting of recurrent torsion, absent contralateral ovary presence, elongated ovarian ligament, and torsion of normal adnexa. 19,40,43 In our cohort, 5 of the 8 recurrences (62.5%) received an oophoropexy during their second presentation, none of which had associated pathology during the initial or subsequent surgery.…”
mentioning
confidence: 81%
“…In doing so, the title of the article would be more congruent and the concept that adnexal torsion is not simply a postmenarchal problem would be strengthened. This is also supported by our recent multicenter study in a pediatric population aged up to 14 years, in which the occurrence of ovarian torsion in the premenarchal period was 67.7% (2).…”
Section: Pediatric Adnexal Torsionsupporting
confidence: 77%
“…We congratulate the authors because their rate of oophorectomy is lower than that observed in our previous retrospective 10-year study (62%), although this result may be susceptible of further improvement (2). This issue was recognized by the authors when they affirm that different approaches to the ischemic-appearing ovaries may affect the rate of adnexal salvage, with teaching hospitals having the highest de-torsion rate without performing oophorectomy (8).…”
Section: Pediatric Adnexal Torsionmentioning
confidence: 77%
“…Half of pediatric patients with ovarian torsion are induced by an ovarian mass, including cystic and solid masses 2–4. Torsion of normal ovary, which can be caused by functional and hemorrhagic cysts, has also been reported 3. In spite of recent progress in diagnostic imaging, an early diagnosis of ovarian torsion is sometimes difficult due to variable clinical symptoms and non-specific imaging findings 3 5.…”
Section: Introductionmentioning
confidence: 99%